Relative bioequivalence of amoxicillin dissolved in breast milk. Issue 3 (20th December 2013) - Yazdani-Brojeni, Parvaneh; Garcia-Bournissen, Facundo; Fujii, Hisaki; Tanoshima, Reo; Ito, Shinya
Abstract : Background: Oral antibiotics use in infants in developing countries is challenging because liquid formulations are often unavailable. However, dissolving solid formulation of drugs in water poses a risk of gastrointestinal infection. Although mother's milk may be a potential vehicle, no evidence exists to indicate that antibiotics dissolved in human milk are bioequivalent to those dissolved in water. Therefore, we compared pharmacokinetic parameters of an orally administered antibiotic, amoxicillin, dissolved in human milk, to those of water-dissolved amoxicillin. Methods: A pharmacokinetic study was conducted in 16 healthy adult volunteers in a randomised crossover design. Marketed amoxicillin powder for suspension was dissolved in either human milk or water at a final concentration of 50 mg/mL, and 10 mL was given orally in a fasting state. Timed blood samples were obtained and plasma amoxicillin was quantified using liquid chromatography-mass spectrometry. Findings: Results showed that pharmacokinetic parameters, including area-under-the-curve, Cmax and half-life of the water-based and milk-based amoxicillin administration were not significantly different. 90% CIs of the ratios of these parameters in concomitant breast milk administration to those of water were within 89% and 116%, suggesting they are bioequivalent (defined as a range between 80% and 125%). Interpretation: We conclude that oral administration of amoxicillin dissolved in human milk at 50 mg/mL results in pharmacokinetics profiles comparable to amoxicillin dissolved in water. Pharmaceutical interactions between amoxicillin and breast milk are unlikely, suggesting no need to modify dosing schedules.